The TNF receptor family member Fn14 is highly expressed in recurrent glioblastoma and in GBM patient-derived xenografts with acquired temozolomide resistance. Issue 10 (20th April 2018) - Hersh, David S; Harder, Bryan G; Roos, Alison; Peng, Sen; Heath, Jonathan E; Legesse, Teklu; Kim, Anthony J; Woodworth, Graeme F; Tran, Nhan L; Winkles, Jeffrey A
Abstract: Background: Glioblastoma (GBM) is a difficult to treat brain cancer that nearly uniformly recurs, and recurrent tumors are largely therapy resistant. Our prior work has demonstrated an important role for the tumor necrosis factor–like weak inducer of apoptosis (TWEAK) receptor fibroblast growth factor–inducible 14 (Fn14) in GBM pathobiology. In this study, we investigated Fn14 expression in recurrent GBM and in the setting of temozolomide (TMZ) resistance. Methods: Fn14 mRNA expression levels in nonneoplastic brain, primary (newly diagnosed) GBM, and recurrent GBM (post-chemotherapy and radiation) specimens were obtained from The Cancer Genome Atlas data portal. Immunohistochemistry was performed using nonneoplastic brain, patient-matched primary and recurrent GBM, and gliosarcoma (GSM) specimens to examine Fn14 protein levels. Western blot analysis was used to compare Fn14 expression in parental TMZ-sensitive or matched TMZ-resistant patient-derived xenografts (PDXs) established from primary or recurrent tumor samples. The migratory capacity of control and Fn14-depleted TMZ-resistant GBM cells was assessed using the transwell migration assay. Results: We found that Fn14 is more highly expressed in recurrent GBM tumors than their matched primary GBM counterparts. Fn14 expression is also significantly elevated in GSM tumors. GBM PDX cells with acquired TMZ resistance have higher Fn14 levels and greater migratory capacity than their corresponding parental TMZ-sensitive cells, and the migratory difference is due, at least in part, to Fn14 expression in the TMZ-resistant cells. Conclusions: This study demonstrates that the Fn14 gene is highly expressed in recurrent GBM, GSM, and TMZ-resistant GBM PDX tumors. These findings suggest that Fn14 may be a valuable therapeutic target or drug delivery portal for treatment of recurrent GBM and GSM patients.